Hubungan Faktor yang Berpengaruh Terhadap Produksi Kerajinan Sepatu di Kecamatan Denpasar Barat - Kesumadinata, Agus Jati; Budiana, Dewa Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2012)
This study aims to determine the effect of labor, working capital, sales price, and technology simultaneously significant effect on the production of a shoemaker in West Denpasar District. The tools that used for data processing multiple linear regression analysis with simultaneously (F test) and partial (t-test). This study have a result that were: to simultaneously show that labor, capital, and technology significantly affect the production of shoes in the district of West Denpasar with a value of coefficients of 0,98. The test results show that partially indicates that the labor variable (X1), working capital (X2), the selling price (X3) and technology (D1) has positive and significant impact on the production of shoes, with significance 0,05.
Keywords: labor; capital; sales price; technology; production; small industry shoemaker